Chapter The Development of Descartes' Idea of Representation by Correspondence - Ben-Yami, Hanoch (Knowledge and its Histories, 2023)
Descartes was the first to hold that, when we perceive, the representation need not resemble what it represents but should correspond to it. Descartes developed this ground-breaking, influential conception in his work on analytic geometry and then transferred it to his theory of perception. I trace the development of the idea in Descartes' early mathematical works; his articulation of it in Rules for the Direction of the Mind; his first suggestions there to apply this kind of representation-by-correspondence in the scientific inquiry of colours; and, finally, the transfer of the idea to the theory of perception in The World.